Modeling academic resilience based on self-compassion and positive self-talk concerning the mediating role of academic well-being among secondary school students - Arezoo Javadi; AliReza Manzari Tavakoli; Hamdollah Manzari Tavakoli; Zahra Zeinaddini Meimand (مجله علوم روانشناختی)
Background: Self-compassion and positive self-talk are two important factors in cognitive characteristics that can play a decisive role in academic performance such as academic resilience, but according to the research, they have been less studied in past research. Based on this, examining the relationship between self-compassion and positive self-talk with academic well-being and academic resilience is a research gap. Aims: So, this research aims to model academic resilience based on self-compassion and positive self-talk concerning the mediating role of academic well-being among secondary school students in Kerman. Methods: The descriptive research method was a correlation type. The statistical population includes all male and female secondary school students in the city of Kerman, with a total of 8200 people in the 2022–2023 academic year. 384 people have been selected as a sample using stratified random sampling. Standard questionnaires were used to collect the data. Data analysis was done with descriptive and inferential statistics of structural equation modeling with SPSS25 and Amos24 software. Results: The model of academic resilience based on self-compassion and positive self-talk has an acceptable fit concerning the mediating role of the academic well-being of secondary school students in Kerman province. Thus, self-compassion and positive self-talk explain 0.67% of the variance in resilience through the mediating role of academic well-being. Conclusion: Based on the findings of the research, among the methods of improving academic resilience and improving the academic well-being of students is strengthening self-compassion and positive self-talk.